Algorithm to Perform a Complete RHS Parametric Analysis for LPP with Bounded Variables (Dhaka University Journal of Science, 2012)
Linear Programming problem (LPP)s with upper bounded variables can be solved using the Bounded Simplex method, without the explicit consideration of the upper bounded constraints. One can consider the upper bounded constraints explicitly and perform the regular righthand- side parametric analysis of LPPs with bounded variables. This paper develops a method to perform the parametric analysis where the upper bounded constraints are considered implicitly, thus reduce the size of the basis matrix.DOI: http://dx.doi.org/10.3329/dujs.v60i2.11521 Dhaka Univ. J. Sci. 60(2): 217-222, 2012 (July)